Temporospatial parameters of gait after obturator neurolysis in patients with spasticity - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2003)
Objective: The management of spasticity should be implemented with the most appropriate pharmacologic agents. Ideally, these agents should provide functional improvement with minimal adverse effects. The aim of this study was to evaluate the width of the base of support and the velocity of gait before and after obturator nerve block. Blocks were performed with aqueous phenol solution in patients with unilateral hip adductor muscle overactivity that resulted in scissoring gait. The goal was to analyze functional improvement and quantify outcomes and to attempt to document adverse effects. Design: This retrospective study analyzed data from 24 patients' files. Inclusion criteria included subjects whose main functional complaint was an adducted gait pattern. All subjects were able to consent for and to undergo unilateral obturator neurolysis with 7% phenol solution. Tempo-rospatial parameters of gait were obtained using the Gait Mat II before and after obturator nerve injection. Results: The analysis showed no statistical change in the walking velocity or step length. However, the width of the base of support was significantly increased after injection. No postblock complications were reported. Conclusion: Obturator neurolysis with 7% phenol solutions is an effective procedure to decrease hip adductor muscle overactivity without reported complications. In the studied population, improvement was found in the width of the base of support without immediate change in walking velocity or step length.
Keywords: gait analysis; spasticity; phenol block; obturator nerve; ADDUCTOR THIGH MUSCLES; NERVE; BLOCKADE; PHENOL